Determinants of materials shortages affecting supply chain: Review on semiconductor manufacturing - Nadarajan, Santhirasegaran; Nadarajah, Gunalan; Bahaudin, Ahmad Yusni (2014)
The purpose of this review to address the actual phenomena on materials shortcomings especially in the semiconductor environment. Materials short supply triggers an alarming for semi-conductor manufacturing which bound to accelerate and affecting production nowadays.This shortcoming will further gives pressure to companies in maintaining productivity and output.Nevertheless in the most devastating condition to upkeep the production plan versus the actual cannot be met due to short supply of materials. Synchronization and smoothing of materials supply is the most concerning and to uphold such practice require drastic remedy to look on the factors that actually contribute this shortcoming.Therefore as being the practitioner for almost two decades in the Japanese base semiconductor environment will try to address the determinants of materials shortages and how should anyone to handle such condition during hand to mouth condition for production.